INTENSI KEWIRAUSAHAAN SOSIAL MAHASISWA KOMUNIKASI SELAMA MASA PANDEMI COVID-19 - Stepanus Bo'do (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2021)
This study aims to answer the question of why during the COVID-19 pandemic the interest in entrepreneurship among young Indonesians is very high. The research seeks to uncover entrepreneurial intentions with an analytical focus on the current dimensions of knowledge, personality, values, and entrepreneurial orientation. The survey was conducted online, attended by 153 students of Communication Science at Tadulako University. The results of the survey data analysis show that in line with efforts to incorporate entrepreneurship courses into the curriculum, entrepreneurial intentions among students are quite high. While the university curriculum is focused on preparing students to become professionals, the Covid-19 situation has encouraged students to contribute to overcoming social problems through social entrepreneurship.